2012
DOI: 10.1021/am3018948
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochromic Ionic Liquid: Design, Characterization, and Performance in a Solid-State Platform

Abstract: This work describes the synthesis and characteristics of a novel electrochromic ionic liquid (IL) based on a phosphonium core tethered to a viologen moiety. When integrated into a solid-state electrochromic platform, the viologen modified IL behaved as both the electrolyte and the electrochromic material. Platform fabrication was achieved through in situ photo-polymerization and encapsulation of this novel IL within a hybrid sol–gel. Important parameters of the platform performance, including its coloration ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 47 publications
6
55
0
1
Order By: Relevance
“…43 Because the H 2 ase was encapsulated within the LBL multilayers, the catalytic reaction occurred near the slide surfaces. 44 Our previous work has revealed that only those optical or electroactive species in the outside layers were active for the catalytic reactions because the LBL multilayers were closely packed or formed aggregates, 30 the structural feature of which prevented the MV 2+ molecules from entering the multilayer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…43 Because the H 2 ase was encapsulated within the LBL multilayers, the catalytic reaction occurred near the slide surfaces. 44 Our previous work has revealed that only those optical or electroactive species in the outside layers were active for the catalytic reactions because the LBL multilayers were closely packed or formed aggregates, 30 the structural feature of which prevented the MV 2+ molecules from entering the multilayer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To solve this problem, bulky counterions were usually selected as it is generally accepted that the melting points of a given ionic liquid (ILs) can be tuned by the size of the counterion . With this method, several π‐conjugated RTILs have been reported where the π‐units were introduced as part of a cation, or anion …”
Section: Introductionmentioning
confidence: 96%
“…[10,11] To solvet his problem, bulky counterions were usually selected as it is generally acceptedt hat the meltingp oints of ag iven ionic liquid (ILs) can be tuned by the size of the counterion. [1][2][3] With this method, several p-conjugated RTILs have been reported where the p-unitsw ere introduced as part of ac ation, [12,[15][16][17][18][19] or anion. [13,14,20] An alternativew ay to lower the melting point of ag iven ionic liquid is to increase the asymmetry of the cation or anion.…”
Section: Introductionmentioning
confidence: 99%
“…[59][60][61] AILs on the other hand, based on alkylimidazolium, phosphonium, and aliphatic quaternary ammonium salts, have been widely studied for use in EDLCs. [44,[62][63][64] The use of AILs is known since long time and they have been extensively used in advanced electrochemical devices like dye sensitized solar cells, [65,66] batteries, [67] electrochromics, [68] and recently in SCs. [69] By contrast, PILs came on the scene relatively late and have been fetching substantial attention from research groups that seek acid free proton activity in solvents.…”
Section: Types Of Ecs and Preference Of Ils Over Traditional Electrolmentioning
confidence: 99%